Multidrug Resistant Tuberculosis (MDR-TB) Factors: Literature Review - Subairi, Moh; Muhith, Abdul; Zahro, Chilyatiz (Journal of Applied Nursing and Health, 2023)
Background: Multidrug-resistant tuberculosis (MDRTB) is the biggest problem in preventing and eradicating TB in the world. MDR-TB occurs if the tuberculosis germs are resistant to various first-line OAT, at least two drugs, namely isoniazid and rifampicin. The emergence of MDR-TB cases presents new obstacles and challenges to the effectiveness of TB control programs due to difficult diagnosis, high rates of therapy failure, and death. This literature review aims to determine the factors that cause multidrug-resistant tuberculosis (MDR-TB). Methods: The method used in this article is a literature review using journal databases from Pubmed and Google Scholar in the 2020-2023 time period with the keywords "drug MDR TB," "multi-drug TB MDR factors," "TB MDR," and " resistant TB medicine" found in 1,990 articles, 304 from Pubmed, and 1,960 from Google Scholar). Articles were selected according to the criteria, and the result was 20 articles ready to be reviewed Results: The results of this study show that risk factors have been proven to show that there is a significant relationship between history of diabetes mellitus, history of TB treatment, patient motivation, adherence to taking medication, duration of TB treatment, status of drug side effects, employment, marital status, economic level, history of contact with patients. MDR TB, stress level, and family support are related to the incidence of MDR TB Conclusion: The conclusion of the 20 articles reviewed shows that age, gender, compliance with taking medication, diabetes mellitus, and a history of contact with MDR TB patients are the factors that most influence the occurrence of MDR TB